Characterization of bioaerosol deposition and emanation in cooling coils - Ong, Walter Tse Yuen (2019)
A final year project report presented to Nanyang Technological University in partial fulfilment of the requirement for the Degree of Bachelor of Engineering (Mechanical Engineering). This project focuses on the characterization of bioaerosol deposition and emanation in cooling coils of ACMV systems.